Analisis Yuridis Pendaftaran Paten dan Merek Dagang bagi UMKM dalam Undang-Undang Nomor 28 Tahun 2014 Tentang Hak Cipta - Ido Pranata Nainggolan (Jurnal Hukum, Administrasi Publik dan Negara, 2026)
Micro, Small and Medium Enterprises (MSMEs) play a strategic role in the Indonesian economy, but still face significant obstacles in intellectual property rights protection, particularly patents and trademarks. This study aims to analyse the legal aspects of patent and trademark registration for MSMEs based on the Indonesian legal framework, with a focus on the implementation of Law No. 28 of 2014 on Copyright and related intellectual property regulations. The research method uses a normative legal approach with a literature analysis of legislation, scientific journals, and the latest statistical data. The results of the study show that the level of patent and trademark registration by MSMEs in Indonesia is still very low, with only 2.3% of MSMEs having registered their trademarks in 2023. The main obstacles include limited legal understanding, high registration costs, complex administrative procedures, and a lack of socialisation. This study recommends simplifying regulations, subsidising registration costs, improving legal education, and strengthening synergy between the government, academics, and MSME actors to improve the protection of intellectual property rights in the MSME sector in Indonesia.